Pemanfaatan Kecerdasan Buatan untuk Inovasi Pemasaran dan Keberlanjutan Bisnis Oleh Oleh Smakelijk - Ronald Farrell Wardhana; Iva Nurdiana Nurfarida; Yoan Santosa Putra (SAFE-Network, 2026)
The culinary souvenir industry in Surabaya faces competitive challenges that demand digital transformation in the era of Society 5.0. This research aims to formulate AI-based marketing innovation strategies to support the business sustainability of